MANAGEMENT OF SUPRA-ERUPTED TEETH IN A PARTIALLY EDENTULOUS PATIENT - Irham M. Adinugraha; Putri Dwi Lestari (Fakultas Kedokteran Gigi Unjani, 2026)
A long period of tooth loss without prosthetic replacement results in significant changes in the oral environment, such as drifting, tipping, and supra-eruption of opposing teeth. Supra-eruption of unopposed teeth reduces the interocclusal space required for denture fabrication, complicating prosthodontic rehabilitation. This case report describes the prosthodontic management of a partially edentulous patient presenting with supra-erupted teeth and reduced interocclusal space using heat-cured acrylic resin removable partial dentures. A 59-year-old female patient presented with missing teeth 15, 14, 24, 25, 37, 36, 46, and 47 due to caries. Clinical and radiographic examination revealed supra-eruption of opposing teeth and reduced interocclusal space. The patient was treated with maxillary and mandibular removable partial dentures fabricated from heat-cured acrylic resin. Shade selection, occlusal bite registration, and denture processing were performed according to standard prosthodontic protocols. Untreated edentulous spaces result in progressive alveolar ridge resorption and supra-eruption of unopposed teeth, which reduces available interocclusal space. The minimum interocclusal space required for removable partial dentures is approximately 8–12 mm; inadequate space compromises denture strength and function. In this case, acrylic resin dentures were successfully fabricated despite limited interocclusal space. Alternative treatment modalities, including orthodontic intrusion and segmental osteotomy, are available for severely compromised cases. Removable partial dentures remain a viable, non-invasive treatment option for partially edentulous patients with moderate supra-eruption and reduced interocclusal space. Early prosthetic intervention is essential to prevent further occlusal complications and maintain oral function. DOI : 10.54052/jhds.v6n1.p127-138